(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This chapter presents a scientific-methodological approach to integrating Project-Based Learning (PBL) and research activities in biology education, specifically for teaching the topic of birds, aiming to overcome the limitations of traditional methods. It analyzes the theoretical foundations of PBL and its advantages in fostering deep understanding, critical thinking, and 21st-century skills. The chapter also discusses applying an organism-centered approach to bird studies, curriculum development, assessment mechanisms, and challenges with solutions in PBL implementation. The proposed model aims to enhance students’ scientific literacy and research skills by engaging them in solving real-world problems.